The Choice of the Leader-Manager Behavioral Model (in the Context of Generations’ Cultural Values Change Out in the Twenty-First Century) - P. V. Trifonov (Управленческие науки, 2016)
A new stage in the life of a society invariably entails drastic changes that have a significant impact on all the spheres of human activity and on the society as a whole. The transition to the information age, which began with the onset of the 21st century, may undoubtedly be considered a qualitative step forward in the society’s development. However, such a transition could not happen without leaving a trace. Computerization and automation of all processes are the main features of the information society. Machines are starting to replace humans wherever technological progress allows for that. In such circumstances, the demand for creative professionals with innovative thinking and multi-tasking ability has significantly increased. Currently, leaders of organizations are facing the challenge of maintaining leadership potential, determined by changing out cultural values of new generations of workers belonging to generations Y and Z. In the article a new model of relations between the manager and the employee as a representative of the new cultural generation is considered one of the tools for managing. The article presents the generation theory of William Strauss and Neil Howe, as well as a brief description of generation Y. The influence of cultural generations change out on management systems in the context of the evolution on the international level and in Russia, in particular, has been analyzed.